European Surveillance System on Contact Allergies (ESSCA): Characteristics of patients patch tested and diagnosed with irritant contact dermatitis - Loman, Laura; Uter, Wolfgang; Armario-Hita, Jose C.; Ayala, Fabio; Balato, Anna; Ballmer-Weber, Barbara K.; Bauer, Andrea; Bircher, Andreas J.; Buhl, Timo; Czarnecka-Operacz, Magdalena; Dickel, Heinrich; Fuchs, Thomas; et al. (Contact Dermatitis, 2021)
Background Irritant contact dermatitis (ICD) is caused by the acute locally toxic effect of a strong irritant, or the cumulative exposure to various weaker physical and/or chemical irritants.
CRIS-Team WoS Importer:2021-05-28